New Peptide Functionalized Nanostructured Lipid Carriers with CNS Drugs and Evaluation Anti-proliferative Activity - Silva, Sara (2022)
Nanoparticulate systems have been widely investigated as delivery vectors for efficient drug delivery in different diseases. Nanostructured lipid carriers (NLC) are composed of both solid and liquid lipids (glyceryl dibehenate and diethylene glycol monoethyl ether) and have demonstrated enhanced biological compatibility and increased drug loading capability. Furthermore, the use of peptides, in particular cell-penetrating peptides, to functionalize nanoparticles and enhance cell membrane permeation was explored in this paper. In this paper, we described the synthesis of a new conjugated of tranylcypromine with MAP. In addition, taking into consideration our previous results, this study developed different NLCs loaded with three central nervous system (CNS) drugs (tacrine (TAC), rasagiline (RAS), and tranylcypromine (TCP)) functionalized with model amphipathic peptide (MAP) and evaluated their activity against cancer cells. Particle size analysis demonstrated NLC presented less than 200 nm and a polydispersity index less than 0.3. Moreover, in vitro results showed that conjugation of MAP with drugs led to a higher decrease in cell viability of a neuroblastoma cell line and Caco-2 cell line, more than MAP alone. Furthermore, NLC encapsulation contributed to higher cellular delivery and enhanced toxic activity at lower concentrations when compared with free or co-administration drug-MAP conjugate.